Socio-economic development of transportation in Fufore, Nigeria - Ahmed Belel, Zaheeda; Ahmed Belel, Waheeda; Abubakar, Mahmoud Hijab; Belel Ahmed, Zainab; Daud, Zawawi; Awang, Halizah (Penerbit UTHM, 2018)
Public transport has a significant influence for the successful economic advancement of a nation. Scarce transportation system restricts the populace potential to take advantage of its natural resources, the distribution of goods and other processed products. Therefore, transportation bears the most premise for growth and economic development in general. The study appraises the effect of Transportation system on the economic advancement of Fufore local government area in Nigeria. The study encompasses five villages which were chosen using multistage sampling technique. About 105 interviewee were also selected and a set of questionnaires administered using random method. Descriptive statistical analysis was used on data obtained. The results of the evaluation indicated that 44.79% of the respondents were farmers. It also revealed that the prevailing mode of transportation in the area is by motorcycles which accompanied by lack of good roads, as more than 65.63% of roads in the area are in a bad condition, makes accessibility to good markets by the respondents difficult for their farm produce, which indirectly also aggravated the cost of transportation. This treand was discovered to have affected the economic activities of the populace thereby increasing the level of poverty in communities of the area. The development of new roads and maintenance of existing ones is recommended to minimise cost of transportation of goods and services thereby abating poverty and fostering economic prosperity